Sanksi Tindak Pidana Pembunuhan Akibat Pengeroyokan dalam Putusan Mahkamah Agung Nomor 101/Pid.B/2018/PN Bau: Analisis Hukum Pidana Islam - Syifa Nurrizkiya; E. Sulyati (IAIN Langsa, 2025)
This condition raises a critical issue regarding the conformity of imposed sanctions with the principles of justice embedded in fiqh jinayah. This study aims to analyze criminal sanctions for murder resulting from collective assault in Decision Number 101/Pid.B/2018/PN Bau from the perspective of Islamic criminal law. This research employs a library-based qualitative approach using normative juridical methods by examining court decisions, statutory regulations, and relevant fiqh jinayah literature. The findings indicate that the sanctions imposed in the decision formally comply with the provisions of Indonesian positive criminal law. Nevertheless, they have not fully reflected the principles of hifz al nafs (protection of life), proportionality, and public interest (maslahah) as emphasized in Islamic criminal law. Therefore, integrating the values of fiqh jinayah into judicial reasoning is essential to enrich criminal sentencing practices and to promote a more just and humane system of punishment.